Transforming Adversity Into Opportunity: Assessing User Satisfaction in Hospital Transformation in Lieu of a Pandemic Through the Multi-Corridor Expansion Model for Epidemic Management and Environmental Design Enhancement - Bhatti, Omer Shujat; Ghufran, Muhammad Asad; Shah, Atta Ullah (Nakhara : Journal of Environmental Design and Planning, 2023)
The COVID-19 pandemic brought the world to a standstill, demonstrating the critical importance of preparedness and adaptation in the face of pandemics and epidemics. Pandemics and epidemics have been a persistent threat throughout human history, causing significant mortality and morbidity, as well as disrupting economies, societies, and politics. The COVID-19 pandemic, caused by the SARS-CoV-2 virus, had a profound impact on healthcare systems worldwide, leading to hospitals transforming into pandemic centers. This case study, conducted at Riphah International Hospital (RIH) in Islamabad, Pakistan, explores the transformation of an existing facility into a pandemic center, highlighting the challenges faced in managing the pandemic conditions and ensuring the safety of the public and medical teams. The study was based on an observational study and data collection from end users with respect to transformation satisfaction and issues faced. Spatial segregation, logistics, air flow control, managing infection control, etc were major challenges faced and managed. Stress was high for the end users who facilitated in medical teams. The study emphasizes the critical importance of preparedness and adaptation in the face of pandemics/epidemics, including the need for specialized training of medical personnel, dedicated COVID-19 units in hospitals, and a robust and resilient healthcare system that can manage future epidemics.